2017
DOI: 10.19126/suje.335877
|View full text |Cite
|
Sign up to set email alerts
|

Sınıf Öğretmenlerinin Mülteci Öğrencilere Yönelik Tutumlarının Çeşitli Değişkenler Açısından İncelenmesi

Abstract: Öz. Bu araştırmanın amacı, sınıf öğretmenlerinin mülteci öğrencilere yönelik tutumlarını incelemektir. Bu amaçla üç alt boyuttan oluşan 24 maddelik Mülteci Öğrenci Tutum Ölçeği (MÖTÖ) geliştirilmiştir. Cronbach Alpha güvenirlik katsayısı .91 olan ölçeğin alt boyutları "iletişim", "uyum", "yeterlik"tir. Ölçek, 2016-2017 eğitim öğretim yılında Sakarya İlinde çalışan 267'si kadın (%53), 234'ü (%47) erkek olmak üzere toplam 501 sınıf öğretmenine uygulanmıştır. Kolmogorov-Smirnov testi sonucunda dağılımların normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(15 citation statements)
references
References 7 publications
0
8
0
7
Order By: Relevance
“…Similarly, research by Nayir (2019) shows that school administrators need linguistic and specialized support as well as social and financial support during the education of immigrant students. Saglam and Ilksen-Kanbur (2017) found in their research on class teachers that teachers did not feel competent about immigrant students and had no professional development plan. Supports implemented show that school administrators do not implement any support for teachers' professional development.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, research by Nayir (2019) shows that school administrators need linguistic and specialized support as well as social and financial support during the education of immigrant students. Saglam and Ilksen-Kanbur (2017) found in their research on class teachers that teachers did not feel competent about immigrant students and had no professional development plan. Supports implemented show that school administrators do not implement any support for teachers' professional development.…”
Section: Discussionmentioning
confidence: 99%
“…Alabay & Ersal (2020) state that this may be due to the fact that teachers' knowledge and skills about children from different cultural backgrounds are not adequate in the classroom. Sağlam & Kanbur (2017) stated in their study that they analyzed teacher attitudes towards refugee children, that they found it more appropriate not to make any changes in the plan. In this direction, it can be said that the teachers' failure to make educational arrangements for children from different cultures in this study may be due to their insufficient knowledge and skills on multiculturalism and planning multicultural education.…”
Section: 2discussion On the Elements Of Multiculturalism In The Classroom Environmentmentioning
confidence: 99%
“…Refugee Student Attitude Scale: The scale developed by Sağlam and Kanbur (2017) consists of three dimensions (communication, adaptation, and efficiency) and 24 items. The total variance explained by the three dimensions was estimated to be 53.61%, and Cronbach's Alpha internal consistency coefficient was found to be .91.…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
“…That's why, integrating children of this age into education will contribute to have lesser problems in later periods. As a matter of fact, Sağlam and Kanbur (2017) pointed to the importance of the primary school age, in which basic knowledge and skills have been given, and the infrastructure of complex learning has been created for the ability of refugee students to hold on to life and to love the country they migrated to. Therefore, it can be claimed that primary school-age refugee students' receiving education together with their peers of different cultural backgrounds is influential not only in their cognitive and affective development but also in their socialization and integration processes.…”
Section: Introductionmentioning
confidence: 99%